Aesthetic properties of Thuluth Al Jali line compositions (The calligrapher Muhammad Nazif is a model) (Journal of the College of Basic Education, 2022)
Link to the art of calligraphy texts Qur'an، the Hadith and the stages of optimization aesthetically، which led to the diversity and multiplicity of forms of Arabic fonts، particularly third line، which is the proficiency master calligrapher of this line، which is the most beautiful and perfect Vtnoat colorful directorial bodies of his lineman to another directory، and become each of them own style in the show built a distinctive design، including calligrapher (Muhammad Nadif) Technical and enabled him to shape and control characters to address the spaces inside the body was prepared in advance، so Me this research studied the aesthetic characteristics of the third evident calligrapher Mohamed Nadif line. Which included four chapters، the first quarter included a research problem and its significance، objectives and limits the definition of terminology، The second chapter tracing the emergence and development of linear composition across historical periods and multiple types، and look at the features of the aesthetic of linear structures according to the multiplicity and diversity of characters، as well as to identify the CV and technical lineman (Muhammad clean)، particularly the aesthetic characteristics of the installation of a third obvious line in accordance with the basics of the design، while the third chapter، such as procedures for research and community research، which amounted to (35) Panel written، were selected (4) models to represent the community، and in which the researcher relied on descriptive approach (content analysis) according to the research of form is analysis، which was built under the guidance of Messrs experts tool، the analysis concluded a number of results that have been allocated the fourth quarter، which showed، investment diversity and multiplicity of forms clips (letters and configurations) for the purpose of the formal closure lined up، and devising aesthetic characteristics in accordance with the basics of the design، and reliability of the geometrical to build a linear designs and does not appear structures (free، Mratah، with a graphical structure، form and content)، and the researcher recommended the need to check the foundations of design as elements of a trade-off in the evaluation of compositions written adoption، and take advantage of the energies of the characters and their movements constructivism، and the definition of the aesthetic characteristics of those involved and interested in the art of calligraphy and ornamentation، and seal researcher Chapter IV proposal to study the aesthetic characteristics of the structures of the third line is clear and top contemporary calligraphers.